The role of public school principals in Ajloun Governorate in building professional learning communities from the teachers’ point of view - Baniata, Oussamh Hassan Ali (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to identify the role of school principals in building professional learning communities in public schools in Ajloun Governorate from the point of view of school teachers. The study used the descriptive survey approach, and a questionnaire was prepared to collect information and was applied to a sample of (367) teachers. They were selected in a stratified cluster method, and the questionnaire consisted from three axes to measure the role of school principals in building professional learning communities The results of the study concluded that there is a (high) role for public school principals in Ajloun governorate in developing professional learning communities from the point of view of school teachers with average (3.71 out of 5), The dimension of vision and shared values was moderated with average (3.67 out of 5) the dimension of supportive and shared leadership was high with average (3.80 out of 5), and the dimension of supportive conditions was moderated with average (3.65), In addition, the findings showed there weren’t any significant differences in the role of school principals in building professional learning communities in public schools in Ajloun Governorate from the point of view of school teachers refers to teacher's sex (male| female) and to teacher qualification. Furthermore there were significant differences at (α ≤ 0.05) refers to years of experiences in favor of (15 years and more). According to the result the study recommended emphasizing the importance of these communities in raising the level of teachers academically, which is reflected on students. It provided decision-makers with a tool that helps them plan the development of these communities by supporting school managers and providing infrastructure and a supportive environment for these communities.
Keywords: Public school principals; professional community development; public school teachers; Ajloun Governorate